Use of Snakes and Ladders Game Media in Multiplication Counting Operations to Improve Students' Understanding in Elementary Schools - Ellyati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Learning while playing is an effort to teach material to students through games and without realizing it students gain knowledge and experience from an easy learning process. This study aims to determine the learning process of multiplication arithmetic operations using the learning media of snakes and ladders game for students. This study aims to determine the learning process of multiplication arithmetic operations using the learning media of snakes and ladders game for students. This type of research is a quantitative method with a pre-experimental design. The sample used was class II-C students at SDN Kembangan Utara 10 Pagi West Jakarta who were selected through the saturated sample technique. In this study using instruments in the form of pre-test and post-test. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Research shows that in the experimental class, the average pretest score is 45.6 and the posttest average score is 80.6. Based on the results of the inferential analysis, the t count value is 0.002 which is smaller than the t table of 3.509 (t count < t table). Thus it can be concluded that H0 is accepted because t count < t table or 0.002 < 3.509 means that there is a significant difference between the results of understanding the multiplication arithmetic operations of students who are taught with snakes and ladders game media in class II students at SDN Kembangan Utara.